Accuracy of self-collection versus cervical sampling for the molecular diagnosis of Chlamydia trachomatis and Neisseria gonorrhoeae in women attending gynecological services - Gabriela Vasco; Cecilia Cruz; Paterson Peñaherrera; Katherine Tipán; Sandy Pila; Karol Guzmán; Marisol Cabascango; Katherine Logacho; Patricio Jácome (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: Successful measures to address the increasing prevalence of sexually transmitted infections (STIs) require practical and accessible education and detection programs. Methods: The ability to detect Chlamydia trachomatis and Neisseria gonorrhoeae may be hindered by a lack of adherence to proper cervical sampling. To address this, we compared the sensitivity and specificity of self-obtained samplings, such as self-collection and first-catch urine samples, to cervical samples taken by a practitioner using the nucleic acid amplification test (NAAT) cobas® 4800 for C. trachomatis and N. gonorrhoeae in 244 women attending gynecological services in Quito, Ecuador. Regardless of sampling method, only 12 patients tested positive for C. trachomatis (4.9% prevalence, 95% CI 2.8 to 8.4%), and no samples tested positive for N. gonorrhoeae. Results: The analysis revealed that self-collection was 100% sensitive (95% CI 66.4% to 100.0%) and 100% specific (95% CI 98.25%-100%), and first-catch urine was 90% sensitive (95% CI 55.5% to 99.8%), and 99% specific (95% CI 96.5% to 99.9%) compared to cervical brushing for the detection of C. trachomatis. No symptoms were associated with a positive C. trachomatis result, highlighting the need for testing even in asymptomatic patients. Furthermore, having a stable intimate relationship in the past year was associated with a negative result for C. trachomatis (χ2 14.01, p < 0.001). Conclusion: This study demonstrates the feasibility and reliability of self-collection and first-catch urine samples as alternative methods for detecting Chlamydia trachomatis and has practical implications for improving STI detection and management programs.